2015
DOI: 10.1016/j.dam.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Scheduling under dynamic speed-scaling for minimizing weighted completion time and energy consumption

Abstract: International audienceSince a few years there is an increasing interest in minimizing the energy consumption of computing systems. However in a shared computing system, users want to optimize their experienced quality of service, at the price of a high energy consumption. In this work, we address the problem of optimizing and designing mechanisms for a linear combination of weighted completion time and energy consumption on a single machine with dynamic speed-scaling. We show that minimizing linear combination… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
(18 reference statements)
0
11
0
Order By: Relevance
“…(Using (17) and Lemma 4) Case III: When At-ALG is (dΦ p /dt) = (dΦ pO /dt) + (dΦ pA /dt). Using (9) and (11), it gives…”
Section: Sub-case (A)mentioning
confidence: 99%
See 1 more Smart Citation
“…(Using (17) and Lemma 4) Case III: When At-ALG is (dΦ p /dt) = (dΦ pO /dt) + (dΦ pA /dt). Using (9) and (11), it gives…”
Section: Sub-case (A)mentioning
confidence: 99%
“…A number of results [4,[7][8][9][10] for online clairvoyant scheduling problems are obtained for the objective of minimising the flow time plus energy. The researchers have good contribution [2,[11][12][13] for the clairvoyant job scheduling problems where the objective is to minimise the weighted/magnitude-based flow time plus energy. The scheduling problems under the nonclairvoyant setting for the objective of minimising the flow time plus energy are studied by some researchers [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…From the previous section, we know that the game admits a pure Nash equilibrium, and by symmetry of the players, in fact two pure Nash equilibria. Following [10], the first one is…”
Section: Convergence Can Take Forevermentioning
confidence: 99%
“…To break the symmetry we consider only points where the social cost of S21 is minimal among the two profiles. In [10] we showed that these are precisely the points that satisfy For such points, we ask whether one of the players wants to deviate from S12, i.e., the other potential equilibrium, with larger social cost. Our experiments indicate that, for each player j ∈ {1, 2}, there is a threshold t j , which depends on p 2 , such that player j wants to deviate if and only if w 2 ≤ t j .…”
Section: Uniqueness Of Nash Equilibriamentioning
confidence: 99%
See 1 more Smart Citation